Hybrid three-dimensional (3D) bioprinting of retina equivalent for ocular research - Shi, Pujiang (2018)
In this article, a hybrid retina construct was created via three-dimensional (3D) bioprinting technology. The construct was composed of a PCL ultrathin membrane, ARPE-19 cell monolayer and Y79 cell-laden alginate/pluronic bioink. 3D bioprinting technology was applied herein to deliver the ARPE-19 cells and Y79 cell-laden bioink to ensure homogeneous ARPE-19 cell seeding; subsequently, two distinctive Y79 cell-seeding patterns were bioprinted on top of the ARPE-19 cell monolayer. The bioprinted ARPE-19 cells were evaluated by prestoblue assay, F-actin, and hematoxylin/eosin (HE) staining, and then the cells were observed under laser scanning and invert microscopy for 14 days. The Y79 cells in alginate/pluronic bioink after bioprinting had been closely monitored for 7 days. Live/dead assay and scanning electrical microscopy (SEM) were employed to investigate Y79 cell viability and morphology. Both the ARPE-19 and Y79 cells were in excellent condition, and the successfully bioprinted retina model could be utilized in drug delivery, disease mechanism and treatment method discoveries.